THE ROLE OF PSYCHOLOGICAL PERSPECTIVES IN DEVELOPING LEARNERS SOCIO-EMOTIONAL COMPETENCIES: A SYSTEMATIC REVIEW - Nisa Mulyana; Amelia Putri Rindiani; Tholkah Syairofi; Rendy Yogo Desayang (P3I UMSurabaya, 2025)
This study examines the role of psychological perspectives in developing students’ social emotional competence through a systematic review of literature published in the last five years. Findings indicate that psychology-based interventions such as emotion regulation training, empathy development, and prosocial behavior facilitation effectively enhance students’ abilities to recognize and manage emotions adaptively. These programs also improve social skills, peer interactions, and reduce anxiety levels within educational settings. Overall, the study highlights the importance of integrating psychological principles into educational practices to promote students’ well-being and sustainable social emotional growth.